KESEHATAN DIRI DAN LINGKUNGAN : PENTINGNYA GIZI BAGI PERKEMBANGAN ANAK - Vyanti, Ades; Yani, Afri; Pratiwi, Beffi Yulinda; Rahmawati, Cindy; Putri, Yecha Febrieanitha (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
This research is entitled Personal and Environmental Health: The Importance of Nutrition for Child Development. The purpose of this study was to determine Personal and Environmental Health: The Importance of Nutrition for Child Development. Development has sequential stages ranging from the ability to do simple things to the ability to do perfect things and each individual has a different speed of development. Research Methods where qualitative analysis activities are carried out interactively and continuously until it is felt sufficient. There are two stages of data analysis in this literature research, namely: analysis at the time of data collection, then analysing the data that has been collected by determining one another. The results showed that nutrition is a component that must exist and its existence is needed by the body, especially in the process of physical growth and development, the nervous system and brain, as well as the level of human intelligence and intelligence. Fulfilment of nutritional needs (nutrients) is the main factor to achieve growth and development results in accordance with genetic potential. Growth is any change in the body that is associated with an increase in physical and structural body size. Meanwhile, development is the increase in ability in the structure and function of the child's body that is more complex. Nutritional status will affect child development. In growth and development, children need nutrients so that the growth and development process runs well.